Study of desorption process from the Zr (62) – Ni (38 wt.%) non-evaporable getter - Aksyonova, G.N.; Bobrov, Yu.P.; Pylypenko, M.M.; Svynarenko, A.P. (Вопросы атомной науки и техники, 2017)
The gas desorption process from the Zr (62) – Ni (38 wt.%) non-evaporable getter produced by the calciothermal technology have been studied. The comparison between the thermostimulated desorption spectra of the samples, which had different prehistory, has shown the history-dependent behavior of spectral line profiles. Variations of the partial pressures of gases released from the getter with temperature increased are presented. Hydrogen bond energies in the hydrogen “traps” have been estimated.